2013
DOI: 10.1371/journal.pone.0058226
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Ovarian Cancer Metastatic miRNAs

Abstract: Serous epithelial ovarian cancer (EOC) patients often succumb to aggressive metastatic disease, yet little is known about the behavior and genetics of ovarian cancer metastasis. Here, we aim to understand how omental metastases differ from primary tumors and how these differences may influence chemotherapy. We analyzed the miRNA expression profiles of primary EOC tumors and their respective omental metastases from 9 patients using miRNA Taqman qPCR arrays. We find 17 miRNAs with differential expression in omen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 51 publications
0
80
1
Order By: Relevance
“…It was demonstrated that high miR-146a expression was able to induce the formation of spheroids from cancer cells in vitro. This process mimics the in vivo intraperitoneal dissemination of cancer cell conglomerates over peritoneal cavities to form metastases (27).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…It was demonstrated that high miR-146a expression was able to induce the formation of spheroids from cancer cells in vitro. This process mimics the in vivo intraperitoneal dissemination of cancer cell conglomerates over peritoneal cavities to form metastases (27).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Cui et al (31) detected downregulation of miR-146a in OVCAR3, CAOV3 and HEY ovarian cancer epithelial cells compared with HOSE cells. To the best of our knowledge, the only previous published study investigating the differences between ovarian primary tumor and metastases in the context of miR expression levels, was performed by Vang et al (27) on 9 paired tissue specimens of primary lesions and omental metastases in serous cancer: Vang et al (27) demonstrated that miR-146a expression level was increased in metastases compared with in primary lesion tissues. It was demonstrated that high miR-146a expression was able to induce the formation of spheroids from cancer cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations